IMPLEMENTASI KEGIATAN PROGRAM KREATIVITAS MAHASISWA BIDANG KEWIRAUSAHAAN (PKM-K) “BLACK HOT (DODOL JAHE)” - Sahbana, Yudhi Aulia; Pratiwi, Ega; Syafitri, Ema; Sari, Purwita (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2023)
The study aims to describe business management including the various innovations carried out in the implementation of one of the 2020 Student Creativity Program in Entrepreneurship (PKM-K) activities that have been carried out virtually. In general, PKM-K activities aim to foster students' understanding and skills in producing unique communities and pioneering profit-oriented entrepreneurship. PKM-K activities are funded by Dikti, namely the "Black Hot (Dodol Jahe)" business. This activity aims to utilize ginger plants to be processed into traditional snacks that are delicious, healthy, and nutritious, as well as opening opportunities in the business of traditional snacks made from ginger. The resulting Black Hot product has health benefits, namely, it can soothe the throat, warm the body, and increase body stamina. The method of activities carried out by the student team is the virtual PKM-K preparation stage, product design making, black hot product manufacture, marketing, and sales stages, evaluation, and reporting stages. The result of the PKM-K "Black Hot" activity is that there is a lot of public interest in buying and tasting traditional snacks with a ginger-flavored variant which sold 30 packs of pre-orders through social media.